Media Pembelajaran Pengenalan Metamorfosis Sempurna Dan Tidak Sempurna Menggunakan Augmented Reality - david kristian lado; Melati Rosanensi (Universitas Bumigora, 2020)
Utilization of Augmented Reality (AR) technology as a learning medium about perfect and imperfect metamorphosis aims as a tool in the alternative learning and teaching process between teachers and students by visualizing 3D objects in realtime. This multimedia application for introducing perfect and imperfect metamorphosis is based on Augmented Reality by referring to the material in the Science books for Elementary School grade IV (Four) curriculum 2013. The methodology used in developing this application is the Luther Sutopo development method. Where this method consists of 6 (Six) stages, namely concept, design, material collecting, assembly, testing, and distribution. The results or the output of the application that the author built is an android application using Augmented Reality technology to show the shape or form of the stages of animals that experience perfect metamorphosis and imperfect metamorphosis. The conclusion of this study is that the overall response of the end user to this application is quite good. Where in some questions related to this AR application has given good answers. This is evidenced by some of the tests that the authors have conducted on applications where the testers are writers and end users.